Newly developed technique and analysis solution to accelerate consolidation of ultrasoft soil. Issue 2 (17th February 2017) - Geng, Chen; Yonghui, Chen; Jiangwei, Shi; Long, Chen
ABSTRACT: Plastic vertical drainage is widely used in vacuum preloading for soft soil treatment. However, plastic vertical drainage has a number of disadvantages such as it only provides drainage paths in vertical directions and the distribution of soil strength is not uniform. A new technique, prefabricated vertical–horizontal drainage, was developed in this study to shorten the consolidation time of ultrasoft soil. Using one vertical drainage tube and four horizontal drainage tubes, prefabricated vertical–horizontal drainage provides drainage paths not only in vertical but also in horizontal directions. An analytical solution was derived to calculate the degree of soil consolidation when using the prefabricated vertical–horizontal drainage technique. Field tests were conducted to evaluate the effectiveness of prefabricated vertical–horizontal drainage and to verify the proposed analytical solution. It was found that consolidation time of soft clays using prefabricated vertical–horizontal drainage was 50% lower than plastic vertical drainage. Moreover, the average undrained shear strength of soil treated by the prefabricated vertical–horizontal drainage technique was approximately 30% larger than that treated by the plastic vertical drainage technique. The degree of soil consolidation estimated from the proposed analytical solution showed good agreement with field measurements. This implies that the proposed analytical solution can be used to directly estimate the degree of consolidation when the soil is treated by prefabricated vertical–horizontal drainage.